Quadrum Galeria de Arte Portugal : Arte Fiera 1977. - Arte Fiera Bologna 1977 (Lisboa : Quadrum Galeria de Arte, 1977)
Moniz, Joao ; Pinheiro, Jorge ; Sena, Antonio ; De Souza, Angelo ; Vieira, Pires ; Da Costa, Noronha ; Sarmento, Juliao ; etc.
Quadrum Galeria de Arte Portugal : Arte Fiera 1977, Bologna, Italia, 1-6 giugno 1977
kunstcatalogus